Psychological predictors of competitive levels in badminton athletes: a gender-stratified analysis - Wang, Yu; Li, Ziyan; Xie, Xianyan; Yang, Gaoyuan; Chen, Tao; Wang, Huiguo (Frontiers in Psychology, 2025)
IntroductionCharacter traits are thought to influence competitive success in racket sports, yet their predictive value for competitive level in badminton and potential gender-specific pathways remain unclear. This study aimed to investigate the predictive role of character traits on competitive level in badminton athletes, with a particular focus on gender-specific pathways.MethodsIn this cross-sectional study, 392 Chinese collegiate badminton athletes (198 men and 194 women) completed the WT Character Inventory for Athletes (WTCAIA). Competitive levels (Unranked, Level 2, and Level 1) were used as an ordinal outcome. Gender-stratified ordered logistic regression models were fitted, adjusting for age and years of training. All models met the proportional odds assumption (p > 0.05).ResultsFor women (Nagelkerke R2 = 0.276), resilience (OR = 1.026, p = 0.022) and flexibility (OR = 1.035, p = 0.002) were significant positive predictors of higher competitive level, whereas sociability (OR = 0.976, p = 0.031) was a negative predictor. For men (Nagelkerke R² = 0.408), resilience (OR = 1.073, p = 0.001) and emotionality (OR = 1.049, p = 0.026) were positive predictors, while sociability (OR = 0.962, p = 0.033) was negative. Resilience and sociability consistently predicted competitive levels across genders, whereas flexibility and emotionality showed gender-specific effects.DiscussionThe higher explanatory power of the models in men suggests structural gender differences in the underlying psychological dynamics. These findings provide empirical evidence for integrating character-based assessments into badminton talent identification and for guiding the development of tailored psychological training strategies that support athlete development.